Demand shock, speculative beta, and asset prices: Evidence from the Shanghai-Hong Kong Stock Connect program - Liu, Clark; Wang, Shujing; Wei, K.C. John (Journal of Banking & Finance, 2021)
Upon the announcement of the Shanghai-Hong Kong Stock Connect program, connected stocks in the Shanghai Stock Exchange experience significant value appreciation of 1.8% over a seven-day announcement window and significant increases in turnover and volatility compared with unconnected stocks with similar firm characteristics, especially for stocks with higher market beta. The beta effect on stock prices is stronger for stocks with higher beta-to-idiosyncratic variance ratios and is reversed within three months. The results support the speculative nature of beta and the multiplier effect of speculation on demand shocks as predicted by Hong, Scheinkman, and Xiong (2006) and Hong and Sraer (2016). The announcement of the Shenzhen-Hong Kong Stock Connect program serves as an out-of-sample test and confirms our findings.